Communication in real-time: ESL students' perception of "Time Out" role play - Fong, L.K. (Universiti Putra Malaysia, 2018)
Many ESL students struggle with communicating English language orally. The purpose of this study is to examine the effectiveness of a new role play technique which enhances speaking activities in the ESL classroom. "Time Out" role play provides students with opportunities to communicate freely and spontaneously in real-life situations. The researchers utilised a qualitative research design where 94 students (Form 4 and 5 classes) in a secondary school in Perak experienced this role play in classroom setting. Qual + qual mix-method was adopted where the dominant (big "Q") is observation and interview. The supplement (small "q") denotes grounded theory open coding. The data was collected from observations, open-ended questions and interviews with selected candidates. Three themes emerged which included influential experience learning, learning by force/compulsion and learning by observation. Role play is said to improve communication skills, enhance vocabulary and induce students for real-life communication. Time Out role play provides that opportunity for all students to communicate spontaneously within real-life like communicative situations. The result of this study indicates that Time-Out role play is successful in achieving the objectives set forth in the Oral Proficiency in English for Secondary Schools (OPS-English) and communication aspiration outlined in the National Education Blueprint (2013-2025). Â© Universiti Putra Malaysia Press.